CONSUMER TO CONSUMER INTERACTİON EFFECTS ON CONSUMER POST-PURCHASE SATİSFACTİON (Third Sector Social Economic Review, 2016)
From the beginning of the human life, while consumption process was an essential tool for the continuity of life, it has become the most important goal in the modern life. But, because of the limited income, consumers have to give rational decision and they have to use their income to increase their life quality. Therefore, consumers can do these rational decisions with experienced and proposal of people who have used the same goods and services. So far, after income it has seen thebiggest factor which effects consumers’ behavior. The aim of this study investigated consumer interaction with other consumer and how effects the consumer to consumer interactions on consumer post purchase satisfaction. The sample of the study consists of consumers who live inKastamonu. A total of 800 consumers (with an approximate 80.0 percent participation rate) are participated in the study on a voluntary. Data were collected through a demographic information form, “consumer – to – consumer interaction scale” developed by researchers to determinethe consumers interaction with other consumers, “factors affecting consumer behavior questionnaire” and “consumer buying behavior factors scale” (Erciş et al. 2007).The structural validity of the consumer to consumer interaction scale was investigated by exploratory and confirmatory factor analysis. According to the analysis, correlation and hierarchical regressionanalysis was used to determine the effects of consumers’ post-purchase satisfaction levels. The results observed that consumer to consumer interaction has an impact predictors of consumers’ post-purchase satisfaction levels(p
Keywords: consumer; consumption; consumer to consumer interaction; consumer satisfaction; post-purchase satisfaction